ANALISIS MANAJEMEN RANTAI PASOK KOMODITI TEH PADA PT. RUMPUN SARI KEMUNING DI KARANGANYAR - Dhea Gusliana; Yohanes Djoko Sunarso; Sunarso Sunarso (Universitas Slamet Riyadi, 2020)
PT. Rumpun Sari Kemuning is a company that produces products in the form of semi-finished tea. The purpose of this reseach is to determine the supply chain performance that is being carried out and to determine the optimal supply chain impact for the company. This research is a case study. The type of data used is qualitative data and quantitative data. Data sources use primary and secondary data. This research uses interview, observation, and literature studies as well as documentation in the data collection. Supply Chain Management Management at PT. Rumpun Sari Kemuning which involves farmers, PT. Rumpun Sari Kemuning, distributors, retailers, and markets have not run well and optimally. The supply chain that has been carried out actually has clear objectives and chain members who carry out their duties according to their roles, but in the supply chain the support from the supporting parties still cannot be felt by some chain actors, especially farmers, as well as limited technological resources can overcome the product flow which decreases during the long dry season.